The role of salesperson emotional behavior in value proposition co-creation. Issue 5 (8th February 2021) - Johnson, Catherine; Kaski, Timo; Karsten, Yvonne; Alamäki, Ari; Stack, Suvi
Abstract : Purpose: This paper aims to focus on how salespeople use emotions to build connections and facilitate value proposition co-creation (VPCC) in B2B complex services sales. Design/methodology/approach: This paper uses video recordings of authentic B2B sales meetings in a two-part qualitative study. Findings: This paper proposes a set of salesperson emotional behaviors that influence the co-creation of value propositions with customers. This paper uncovers five salesperson emotional behavior archetypes influencing VPCC. Research limitations/implications: This study advances the value proposition literature by linking salespeople's emotional behaviors with micro-level activities in the collaborative crafting of value propositions. The unique methodology may encourage researchers to apply video recordings in future studies. Practical implications: The study provides managerial guidelines for improved selling competence and sales team organization. Originality/value: This study's findings represent a new insight into the actual manifestations of salesperson emotional behaviors that are commonly discussed but rarely observed directly.